2009
DOI: 10.1177/0192513x09345833
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents With Two Nonresident Biological Parents: Living Arrangements, Parental Involvement, and Well-Being

Abstract: We know little about children who have two living nonresident biological parents. Using data from the National Longitudinal Study of Adolescent Health, this study examines the diverse living arrangements of U.S. adolescents in this situation, the kinds of relationships they have with each of their nonresident parents, and how these living arrangements are associated with adolescent wellbeing. Differences between these adolescents (N = 502) and those who have one nonresident biological parent (N = 4746) are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Finally, is the higher contact of non-resident repartnered mothers due to a selection effect moving in the opposite direction to that of non-resident repartnered fathers, or to inadequate control of differences in their new family (i.e., new children)? Alternatively, can we hypothesize that in Italy when the mother can count on having a new own family, a gender effect that considers women to be the nurturers of children (King, Stamps, and Hawkins, 2010) is operating? These and other questions may drive further longitudinal studies that aim to overcome a purely descriptive approach.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, is the higher contact of non-resident repartnered mothers due to a selection effect moving in the opposite direction to that of non-resident repartnered fathers, or to inadequate control of differences in their new family (i.e., new children)? Alternatively, can we hypothesize that in Italy when the mother can count on having a new own family, a gender effect that considers women to be the nurturers of children (King, Stamps, and Hawkins, 2010) is operating? These and other questions may drive further longitudinal studies that aim to overcome a purely descriptive approach.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to children with biological fathers in the household, children without fathers or those who do not live with their biological fathers were found to be less prepared for school (Fowler & Richards, 1978;Martin et al, 2010), to have lower academic achievement and cognitive ability (Cherlin & Furstenberg, 1994;Hetherington & Stanley-Hagan, 1997;Mulkey, Crain, & Harrington, 1992;Rodgers & Rose, 2001), to experience higher risk of school dropout (McLanahan & Sandefur, 1994;Suh & Suh, 2011), and to exhibit higher levels of behavior problems (King, Mitchell, & Hawkins, 2010). For instance, Menning (2006) found that when nonresident fathers had higher involvement in their children's lives, those children had a lower probability of detrimental school outcomes; the students who were most at risk were those whose fathers had infrequent involvement.…”
Section: Father Residencymentioning
confidence: 99%
“…They may have had the disadvantages that often come with a single-mother household, such as low SES, lack of father involvement, and perhaps lower mother involvement, especially if the mother is working long hours to support her child or children. Adolescents also have lower socioemotional stability and experience negative feelings toward their fathers when their fathers are not available to support them emotionally, academically, spiritually, or physically (Downey, Ainsworth-Darnell, & Dufur, 1998;King et al, 2010;Menning, 2006;Popenoe, 1999;Sweeney, 2007).…”
Section: Adolescents Without Resident Fathersmentioning
confidence: 99%
“…Yet most studies of nonresident parent involvement have been limited to children with a resident parent and examine, for example, the effects of a stepparent (Buchanan, Maccoby, & Dornbusch, 1996). Despite lower child well‐being and higher rates of poverty (King, Mitchell, & Hawkins, 2010; Sun, 2003), little is known about nonresident parent involvement for children with two nonresident parents who live with grandparents, relatives, or nonrelatives.…”
mentioning
confidence: 99%